Repression in the digital age surveillance, censorship, and the dynamics of state violence - Gohdes, Anita 1986- (Oxford University Press, 2024)
In 'Repression in the Digital Age', Anita R. Gohdes provides an in-depth look into the relationship between digital technologies and state violence. Drawing on original data, Gohdes argues that mass access to the Internet presents governments who fear for their political survival with a set of response options, which in turn support different forms of violence by state forces. As digital communication has become a bedrock of modern opposition and protest movements, this text breaks new ground in examining state repression in the information age. -
Keywords: Autoritärer Staat; Politische Verfolgung; Neue Medien; Protestbewegung; Unterdrückung; Internet; Internet / Political aspects; Information technology / Political aspects; Internet and activism; Protest movements; Political persecution; Authoritarianism; Internet / Aspect politique; Technologie de l'information / Aspect politique; Cybermilitantisme; Répression politique; Autoritarisme